Visual information: theoretical foundations and mechanisms of action - Turzhan, О.І.; Yegemberdiyev, И.Д.; Ibrayeva, Э.Е. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2020)
This article discusses the mechanisms of application of visualization in PR information and image, advertising and marketing information and its scientific basis. The mechanisms of influence on the dissemination of invisible information have been studied in visible form, as well as the scientific concepts that determine their basis. The perception of information through the eidosphere is very beneficial for the consumer, and theoretical and methodological conclusions about its visibility and interactivity are a necessary technology for business. Interactivity, media-psychological, mental aspects of stereotypical, symbolic signs used in visual information, the mechanism of interaction between visualization and time management are important objects of our research article.Visual information is understandable to people of all languages without a translator and gives an aesthetic appeal to the target audience. The article analyzes in detail all these important aspects. At the end of the article, there are several links to the simplest and most effective tools available for creating visual information